Kinase-dependent regulation of ciliary protein transport and its implications for therapy - Chaya, Taro; Ayano, Yuri; Furukawa, Takahisa (Frontiers in Molecular Biosciences, 2025)
Primary cilia are evolutionarily conserved microtubule-based structures that extend from the surfaces of many different cell types and decode a wide range of extracellular chemical and physical stimuli. Ciliary defects cause human diseases, termed ciliopathies, which are characterized by a variety of symptoms, such as developmental and sensory abnormalities. The formation and function of primary cilia depend on intraflagellar transport (IFT), which is a bidirectional protein transport system coordinated by three multi-subunit protein complexes with kinesin and dynein motors along the ciliary axoneme. Accumulating evidence has demonstrated that several serine-threonine kinases play key roles in the regulation of IFT. Here, we review the current understanding of the roles of these kinases during the IFT process, as well as their regulatory mechanisms, physiological and pathophysiological significance, and potential to treat ciliopathies and age-related obesity.